Z Generation's Perception On The Film Fast N Furious: Fast X To Listening Comprehension In Tangerang Area - Nadya Oktaviani Nugraha; Arjulayana Arjulayana; Imtihan Hanim; Dyah Supraba Lastari (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
Listening comprehension is an essential component of language learning, particularly for non-native English speakers. Films, one of the most popular multimedia formats among Generation Z, to help their listening abilities. This study aims to identify Generation Z by using the movie Fast n Furious: Fast X in listening skills and find out the factors that influence Generation Z's perceptions of using the movie Fast n Furious: Fast X in learning English to listening. This research uses qualitative approach with some instruments of the research such as; interviews, observation, listening tests, and documentation. For the sample taken by the researcher, there were 15 respondents, and the basis taken in choosing the sample was Generation Z whose age range was from 16-25 years. For the number of interviews the researcher gave, there were 10 questions. In addition, in collecting this data, researchers conducted observations for 2 weeks. The results of the research on movie usage show that, for Generation Z, watching Fast & Furious: Fast X is essential for improving listening skills as it can help children's character development. In addition, the movie can support students' understanding of different languages and contextual learning approaches. How Generation Z considers using Fast & Furious: Fast X to learn English through listening is revealed by the research findings on the perceptual element with the movie. Almost 100% of the participants said that the movie provided more scenarios and imaginative ways to learn the language while acquiring English. Watching the movie can help viewers become more proficient listeners as some of the jargon used in the dialog is straightforward and every day.Â Keywords: Perception, Generationâ€™s Z, Film, Fast n Furious: Fast X, Listening Comprehension